Respuesta :

Answer:

Explanation:To find the average rate of change for

=

6

sin

(

2

)

r=6sin(2θ) over a given interval, we need to compute the change in

r with respect to

θ and then take the average over that interval.

Given

=

6

sin

(

2

)

r=6sin(2θ), we'll first find

dr

:

=

6

sin

(

2

)

r=6sin(2θ)

We'll use the chain rule:

=

(

6

sin

(

2

)

)

dr

=

d

(6sin(2θ))

=

6

cos

(

2

)

×

2

=6cos(2θ)×2

=

12

cos

(

2

)

=12cos(2θ)

Now, to find the average rate of change over an interval, say

[

1

,

2

]

1

2

], we use the formula:

Average rate of change

=

(

2

)

(

1

)

2

1

Average rate of change=

θ

2

−θ

1

r(θ

2

)−r(θ

1

)

But here,

(

)

=

6

sin

(

2

)

r(θ)=6sin(2θ), so the average rate of change becomes:

6

sin

(

2

2

)

6

sin

(

2

1

)

2

1

θ

2

−θ

1

6sin(2θ

2

)−6sin(2θ

1

)

This expression gives the average rate of change of

r with respect to

θ over the interval

[

1

,

2

]

1

2

].

To find the average rate of change for

=

6

sin

(

2

)

r=6sin(2θ) over a given interval, we need to compute the change in

r with respect to

θ and then take the average over that interval.

Given

=

6

sin

(

2

)

r=6sin(2θ), we'll first find

dr

:

=

6

sin

(

2

)

r=6sin(2θ)

We'll use the chain rule:

=

(

6

sin

(

2

)

)

dr

=

d

(6sin(2θ))

=

6

cos

(

2

)

×

2

=6cos(2θ)×2

=

12

cos

(

2

)

=12cos(2θ)

Now, to find the average rate of change over an interval, say

[

1

,

2

]

1

2

], we use the formula:

Average rate of change

=

(

2

)

(

1

)

2

1

Average rate of change=

θ

2

−θ

1

r(θ

2

)−r(θ

1

)

But here,

(

)

=

6

sin

(

2

)

r(θ)=6sin(2θ), so the average rate of change becomes:

6

sin

(

2

2

)

6

sin

(

2

1

)

2

1

θ

2

−θ

1

6sin(2θ

2

)−6sin(2θ

1

)

This expression gives the average rate of change of

r with respect to

θ over the interval

[

1

,

2

]

1

2

].

ACCESS MORE